Continuous dependence on initial data and high energy blowup time estimate for porous elastic system - Jiangbo Han; Runzhang Xu; Chao Yang (Communications in Analysis and Mechanics, 2023)
In this paper, we establish two conclusions about the continuous dependence on the initial data of the global solution to the initial boundary value problem of a porous elastic system for the linear damping case and the nonlinear damping case, respectively, which reflect the decay property of the dissipative system. Additionally, we estimate the lower bound of the blowup time at the arbitrary positive initial energy for nonlinear damping case.